Appraising Grammar Mistakes in English Students’ Written Recount Text - Hasan Hasan; Usman M; Muhammad Hanafi (Universitas Muhammadiyah Enrekang, 2023)
This study aims to find out the most frequent errors students make in writing recount texts. This study used a descriptive method with quantitative data analysis techniques to answer the questions posed. The scope of this research is limited to the grammatical analysis and writing mechanism of the components of the fourth recount text written by third year students of UMS Rappang. These errors are classified into six categories: errors in the use of verb forms; thr use of the article; use of prepositions; noun pluralization; use of pronouns; use of conjunctions. The findings of the study showed that the most frequent errors students made were in the use of verb forms, punctuation marks, prepositions, nouns, articles and pronouns. It can be concluded that students have not mastered grammar well. They face many problems in English in general and in writing English in particular.